FACTORSINFLUENCINGSTUDENTS'LEARNINGOUTCOMESIN BASICACCOUNTINGCOURSESINGRADEXSMKLABOR FKIP UNRIPEKANBARU - Arief Fatahilla; Suarman Suarman; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:Thepurposeoftheresearchistoknowwhatfactorsaffecttheoutcomeofstudents'learninginbasicgradeXaccountingsubjectsatSMKLabortargetFKIPUNRIPekanbaru.ThepopulationinthisstudyistheentireclassXstudentaccountingandfinanceinstitutionofthe2018/2019academicyearInstituteatSMKLaborPartnerFKIPUniversityRiauPekanbaruandthesamplesthatwillberesearchedasmanyas49students.Datacollectionusingquestionnaires.Analysisofdatausingthedeskrificanalysisoftheprosentase.Thepurpose ofthe studyisto know thedominantfactorsaffecting theoutcomeoflearning.Basedontheresearchshowedthatthedominantinternalfactorshowingthelearningresultsisthelearningmotivationfactorwiththemeanvalueof2.7,learninghabitswithmeanvalue2.54,attitudeinlearningwithmeanvalue2.20andlearninginterest2.15whilethedominantexternalfactoristhefamilyenvironmentwithmeanvalue3.25,theschoolenvironmentwithavalueof2.81andfriendsassociatewiththemeanvalueof2.33.KeyWords:InternalandExternalFactors,LearningOutcomes